2008
DOI: 10.1177/0022427808317573
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Rates and Causes of Death of Convicted Dutch Criminals 25 Years Later

Abstract: Extant theory hypothesizes that offenders have greater risk of premature and unnatural death than nonoffenders, but few studies have assessed this hypothesis; those doing so have relied on U.S. samples of male offenders typically followed until midlife. This article examines the relation between criminal conduct and mortality rates in the Netherlands using data from the Criminal Careers and Life Course Study, which traces the life course and criminal careers of 4,615 males and females convicted in 1977 up unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 43 publications
8
39
0
Order By: Relevance
“…These findings testify to the importance of age at criminal debut [13] as well as to the serious mortality risk associated with illegal drug involvement [17]. Our results are also in concordance with Nieuwbeerta and Mortality in sentenced offenders 239 Piquero [7] who found that more active and more chronic offenders ran a substantially higher risk of early death. Previous incarceration did not remain a significant predictor in any of the multivariable analyses, neither in males nor in females, nor in any specific cause of death.…”
Section: All-cause Mortalitysupporting
confidence: 89%
See 1 more Smart Citation
“…These findings testify to the importance of age at criminal debut [13] as well as to the serious mortality risk associated with illegal drug involvement [17]. Our results are also in concordance with Nieuwbeerta and Mortality in sentenced offenders 239 Piquero [7] who found that more active and more chronic offenders ran a substantially higher risk of early death. Previous incarceration did not remain a significant predictor in any of the multivariable analyses, neither in males nor in females, nor in any specific cause of death.…”
Section: All-cause Mortalitysupporting
confidence: 89%
“…Less is known about the mortality in the much larger population of sentenced criminal offenders, many of whom have never been incarcerated. To our knowledge only one large-scale comprehensive study has been carried out on the mortality in convicted offenders [7]. In this study a Dutch cohort of 4,615 criminal offenders who were convicted in 1977 was followed up 25 years later, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For example, among adult offenders, frequent, chronic criminal conduct has been associated with early and unnatural death. 27 A recent longitudinal study found that youth who underwent official juvenile court processing (versus being diverted out of the justice system) had a higher rate of future violent and non-violent crimes and were more likely to have an adult criminal record. 28 Moreover, in a 50-year follow-up study of both offenders and community youth, 29 alcohol use and committing greater numbers of severe offenses were associated with higher mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Nieuwbeerta and Piquero 2008). For example, Farrington's (1995) analysis of males participating in the Cambridge Study in Delinquent Development revealed that offending was predictive of a wide array of poor health outcomes.…”
Section: New Trends In Criminal Careers Researchmentioning
confidence: 99%